PENINGKATAN HASIL BELAJAR MATERI PENYESUAIAN MAKHLUK HIDUP DALAM PEMBELAJARAN KOOPERATIF METODE THINK-PAIR-SHARE DIPADU DENGAN METODE PICTURE AND PICTURE PADA SISWA KELAS V-A SD MUHAMMADIYAH 8 DAU MALANG - Citra Marina; Ainur Rofieq; Sri Wahyuni (JPBI (Jurnal Pendidikan Biologi Indonesia), 2015)
PENINGKATAN HASIL BELAJAR MATERI PENYESUAIAN MAKHLUK HIDUP DALAM PEMBELAJARAN KOOPERATIF METODE THINK-PAIR-SHARE DIPADU DENGAN METODE PICTURE AND PICTURE PADA SISWA KELAS V-A SD MUHAMMADIYAH 8 DAU MALANG Citra Marina1, Ainur Rofieq1, Sri Wahyuni1, 1Program Studi Pendidikan Biologi, FKIP, Universitas Muhammadiyah Malang email: biologi.umm@gmail.com ABSTRACTFrom interviews result, we can say 45% of the number of students has a low learning outcomes. The research purposes are: To determine the increase in the learning material adjustment Beings through cooperative learning combined the TPS method with P & P method at the VA graders SD Muhammadiyah 8 Dau Malang. Implementation of TPS learning combined with P & P already performing optimally. Based on the results of correcting data analysis sheet formative test on cycle-3 students who scored> SKM as many as 27 people (90%),whereas the received value <SKM value of 3 people (10%) of 30 students. Keywords: Think-Pair-Share (TPS), Picture and Picture (P&P), Cooperative